Pandangan Siswa Akan Penggunaan Tamasya Daring Sebagai Media Belajar untuk Siswa SD di Sukodono - Premitha Evi Noviana; Ettyani (STKIP PGRI SIDOARJO, 2022)
Since the COVID-19 pandemic spread in the world especially Indonesia,, people have to adapt with the new condition. When all of the activities must be done in online, including the learning process. There are so many schools and teacher that look for the most suitable media in learning pocess. From then on, researchers make a research, in a collaboration with PKM team, to help teacher and students get a suitable media in learning process. This research discusses about student’s perception on virtual tour as the learning media. The mix method is used in collect the data, by using some questionnaires and interviews, researchers process the data until get a conclusion. From the result data can be conclude that using virtual tour can help teacher serve a new media in teaching their students.